Status of Job Involvement in the Financial Sector of Nepal - Shrestha, Prakash; Prajapati, Archana (Journal of Balkumari College, 2022)
The main objective of this study is to investigate how employees perceive their level of job involvement in the financial sector of Nepal. Descriptive and analytical research designs have therefore been used in this study. To achieve the research goals, a set of research questions are created to elicit the opinions of employees. A total of 240 questionnaires—40 in each of the 6 institutions, which include 3 commercial banks and 3 insurance companies—are distributed for this purpose. 193 (80.41%) of the copies of the survey are fully completed and returned. These questionnaires are used for the research's objectives. These responses have been gathered from the chosen financial institutions' corporate, branch, and head offices. Results show that most of the employees perceive a moderate level of job involvement toward their organizations. In the case of ownership pattern, the Nepalese public sector shows higher job involvement than that of the private sector. The results further show that perceived job involvement has significant associations with all demographic characteristics that have been analyzed. This means there are different demographic effects on employees’ perceived job involvement. In the case of the banking and insurance sector, insurance sector employees hold a relatively higher level of job involvement than the banking sector employees. High-involvement workers struggle to keep work and personal life apart because they care so much about what they do. Employees' attitudes and behaviors, which in turn affect their work performance and the success of the company, are influenced by how involved they feel in their jobs. As a result, job involvement research is crucial for Nepalese workplaces.